Genesis of chronic pain. Issue 9 (September 2016) - Seth, Bharti; de Gray, Lorraine
Abstract: The theories behind the evolution of the genesis of chronic pain are explored from a historical perspective. The major focus of the article explores the biomedical and the psychosocial factors that contribute to the genesis of chronic pain in particular how the physical and psychological interact together. Risk factors and pre-existing determinants are discussed.